Konsep Insan Kamil dalam Perspektif Imam Al-Ghazali dan Siddhartha Gautama: Studi Komparatif - Pratama, Sihab Fajar; Supriadi, Yogi; Hakim, Maman Lukman (FASTABIQ: JURNAL STUDI ISLAM, 2024)
Humans are beings endowed with the ability, privilege, and responsibility to explore deeper aspects of life. Their inherent nature to think and question serves as a distinctive trait. To adapt to life, individuals must understand themselves and differentiate between good and evil. This study aims to analyze the concept of the perfect human according to Imam Al-Ghazali and Siddhartha Gautama. A descriptive approach is employed with a library research method, utilizing books and other literature-based sources.Imam Al-Ghazali posits that the essence of humanity is primarily determined by its spiritual elements, which elevate humans above other creatures, including angels. However, neglecting these elements can degrade humans below the level of animals. Al-Ghazali identifies four key spiritual components: al-'aql (intellect), al-qalb (heart), al-nafs (soul), and al-ruh (spirit). Conversely, Siddhartha Gautama emphasizes the mind as the core of human existence, comprising feelings, thoughts, memories, and consciousness. The findings reveal that despite their distinct cultural and philosophical backgrounds, both thinkers underscore the significance of non-material elements as the foundation of human excellence. This study contributes to a deeper understanding of the concept of humanity across traditions and highlights its relevance to contemporary discussions on ethics and human development.Keywords: Al-Ghazaly; Perfect Human;  Sidharta Gautama; Spirituality